Recent progress and challenges in potassium-ion battery anodes: towards high-performance electrodes - Jeseon Lee; Juyeon Lee; Eunho Lim (Science and Technology of Advanced Materials, 2025)
With the growing demand for lithium-ion batteries (LIBs) and the rising cost of lithium (Li) resources, potassium-ion batteries (KIBs) have emerged as promising alternatives due to their abundant potassium (K) reserves, cost-effectiveness, and electrochemical similarities to LIBs. However, the commercialization of KIBs hinges on the development of high-performance anode materials with improved capacity, stability, and rate capability. This review provides a comprehensive overview of KIB anode materials, with a particular focus on the key reaction mechanisms, including intercalation, alloying, and conversion. Various material strategies, including carbonaceous structures, metal-based alloys, and conversion-type compounds, are discussed in terms of their advantages, limitations, and recent advancements. Additionally, challenges such as volume expansion, sluggish kinetics, and long-term stability are examined, along with strategies to overcome these issues. Future research directions are also highlighted, including electrolyte optimization, interface engineering, and K metal anodes, which hold great potential for increasing energy density but require solutions for dendrite formation and Coulombic efficiency. By summarizing the latest developments and challenges, this review aims to provide insights into the future design and optimization of KIB anodes for next-generation energy storage systems.